Urban livestock keeping: Leveraging for food and nutrition security - Lindahl, Johanna F.; Magnusson, Ulf; Grace, Delia (Elsevier, 2019)
In spite of the importance of urban livestock keeping in providing the urban populations with livelihoods and nutritious foods, this phenomenon does have both benefits and negative effects. Here we explore the different strengths and weaknesses of urban livestock systems, including the risks for transmission of diseases and contribution to poor sanitation. In addition we look at the opportunities and threats that urban livestock keeping may face in the future, which are often dependent on policies and public attitudes.